Global analysis of transcription factors using both the reference genome and the multi-transcriptome of Akebia trifoliata reveals a sophisticated functional strategy - Yang, Hao; Li, Jie; Zhong, Shengfu; Yang, Huai; Han, Rui; Yi, Xiaoxiao; Li, Xueying; Luo, Peigao (Frontiers in Plant Science, 2025)
IntroductionAll the transcription factors (TFs) encoded by a genome collectively constitute a functional entity that closely regulates various life activities through mutual cooperation. Akebia trifoliata, which has great industrial and medicinal value, has significant potential as a model plant for use in perennial horticultural studies, and its TF repertoire must be comprehensively resolved.MethodsWe identify all TFs from the A. trifoliata reference genome via DBD homology matching, subsequently characterizing their chromosomal distribution, gene structure, protein properties, and binding motifs, while further employing all available RNA-seq data to assess TF family conservation and infer potential interactions through co-expression analysis.ResultsThe TF repertoire of A. trifoliata consists of 1602 transcription factors from 56 families, revealing uneven chromosomal distributions and variations in gene structure, GC content, molecular weight, and evolutionary features such as duplication and selection strength. Functional annotation indicated that these TFs play diverse regulatory roles in various biological pathways, despite members within the same family often having similar functions. The expression profile data further supported the pleiotropic nature of many TFs, and their tissue-specific expression modules and functional enrichment were characterized. Notably, cooperative interactions were frequently observed within and across TF families, and some of these interactions were highly credible, as identified by co-expression analysis. Additionally, among all of them, variant sites were detected in 1473 TFs, whereas variant sites were not detected in 129 TFs.DiscussionThis comprehensive analysis offers valuable insights into the regulatory mechanisms of A. trifoliata, enhancing our understanding of TF interactions and their roles in the development and adaptability of this organism.